Reversible Hypothermia in a Drug-naive Inpatient with Alzheimer’s Disease Receiving Pipamperone - Kamp, D.; Paschali, M.; Lange-Asschenfeldt, C. (Pharmacopsychiatry, 2016)
Hypothermia is a potentially life-threatening side effect of antipsychotic drugs, especially those with strong 5-HT2 antagonist properties. However, the exact underlying mechanism is still under debate. We discuss a case of hypothermia following pipamperone treatment in an elderly female inpatient with Alzheimer’s disease, which occurred at day 4 after medication onset and vanished after dose reduction. Thus, this case demonstrates 1) the importance of monitoring body temperature even in low-potency antipsychotics, at least in the elderly, and 2) that in some cases, dose reduction may be a sufficient countermeasure.
Keywords: hypothermia; pipamperone; dementia; alzheimer’s disease